Alterations of ATG4A and LC3B in neurons derived from Alzheimer's disease patients. (14th February 2023) - Shirotani, Keiro; Watanabe, Kaori; Hatta, Daisuke; Kutoku, Yumiko; Ohsawa, Yutaka; Sunada, Yoshihide; Kondo, Takayuki; Inoue, Haruhisa; Iwata, Nobuhisa
Abstract: We investigated the alterations in autophagy‐related molecules in neurons differentiated from induced pluripotent stem cells obtained from patients with Alzheimer's disease (AD). Consistent with our previous microarray data, ATG4A protein was upregulated in the neurons derived from a familial AD patient with an APP‐E693Δ mutation who showed accumulation of intracellular amyloid β peptide (Aβ). This upregulation was reversed by inhibiting Aβ production, suggesting that the intracellular Aβ may be responsible for the upregulation of ATG4A. The LC3B‐II/LC3B‐I ratio, an index of autophagosome formation, was lower in the neurons derived from the AD patient with APP‐E693Δ as well as the neurons derived from other familial and sporadic AD patients. These findings indicate that dysregulation of autophagy‐related molecules may accelerate the pathogenesis of AD.